Alasan mahasiswa fakultas kedokteran gigi tidak menggunakan gigitiruan - Eri H. Jubhari (Journal of Dentomaxillofacial Science, 2008)
Edentulous state causes disorders in chewing, esthetic, phonetic, temporomandibularjoint, and the vinicity tissue. As dental students, they must have to replace their teethwith denture. This study aimed to know the reason why dental students of HasanuddinUniversity didn’t use denture. This descriptive study involved 30 samples based onpurposive sampling technique. Data was obtained from questionnaire andexamination of oral cavity. The result showed that 23 samples wanted to use denture,and 26 samples said that the denture was necessary. The reasons of not using denturewere as follows: no time, not disturbed, expensive, fear, and just for orthodontictreatment. It can be concluded that most respondents had known the importance ofusing denture. However, the behavior of using denture had not yet existed because ofexternal and internal factor. For that, it is suggested to socialize the imprtance ofusing denture.